Ultrasound-aided mixing of sponge cake batter - Tan, Mei Ching (2011)
The effect of ultrasound-assisted mixing of cake batter and its effect on baked cakes were studied. The Box-Behnken design was used to optimize the experimental condition of cake batter mixing. This involved three factors, i.e. mixing time, mixing speed and cake loading before conducting experiments with ultrasound application using a commercial mixer. The batter mixing time ranged from 6 to 20 minutes with speed from 90 to 120 rpm, and cake loading from 3 to 5 cakes were chosen for this purpose. A total of 15 runs of experiments with three levels, each attributing to high, central and low, and with additional three replicated center points were conducted. Based on goal settings of minimum batter density, cake density, hardness, gumminess and chewiness; and maximum springiness, cohesiveness and resilience, the optimum and feasible batter mixing required 9 minutes of mixing time at 90 rpm for the loading of 3 cakes. The high power ultrasound bath system was then set up to be used as a processing aid during mixing. The bowl of the existing mixer system is located at the center of the ultrasonic bath tank filled with water. The power ultrasound of 1 kW, 1.5 kWor 2.5 kW can take effect for the entire or partial mixing period. It is generated by two generators, and five units of flange type piezoelectric transducers mounted on the stainless steel tank. The electric field of energy received in each transducer is contracted by the piezoelectric ceramics in the transducer, expands and leads to pressure waves transmitting through water in the tank to the batter in mixer bowl. The optimum experimental condition determined earlier was then used for mixing of sponge cake batter with different combinations of ultrasound power exposure ranging from I to 2.5 kW, and for duration ranging from 3 to 9 minutes. Ultrasound-aided mixing for 9 minutes at I kW produced lower batter density (0.9%), cake hardness (5.2%) and springiness (0.4%); higher batter viscosity (9.7%), consistency index (l0%), overrun (3%), and cake volume (4.1 %). At 2.5 kW, it produced lower batter density (2.3%) and cake hardness (11.5%); higher batter viscosity (6.9%), consistency index (7.3%), overrun (7.6%), cake volume (1.4%), and springiness (0.3%). However, at 1.5 kW, the lower batter density (0.63%), viscosity (4.1%), consistency index (4.4%) had produced higher batter overrun (0.02%), cake volume (I .8%), and springiness (0.2%) resulting in lower cake hardness (8%). These findings indicate that more air is being incorporated into the food system with the aid of ultrasound application during mixing, and it has directly enhanced the volume and textural properties of cakes. The two-way ANOVA showed that ultrasound duration has the most significant effect on cake volume (P < 0.001), followed by batter density and overrun (P < 0.1), and viscosity (P < 0.5). For cake textural attributes, ultrasound duration and power showed similar significant effects on hardness and springiness at P < 0.5. The ultrasound power and duration showed more significant effects on cake properties than batter properties. In conclusion, ultrasound-aided mixing was able to enhance cake batter mixing process through the improved textural properties of cakes.